Space Law at the Crossroads of Commercial Expansion of Outer Space - N. V. Galitskaya (Евразийская интеграция: экономика, право, политика, 2025)
The main international law governing legal relations in outer space remains the 1967 Treaty, the rest of the space legislation is of an internal national or bilateral nature. And despite the fact that the Outer Space Treaty prohibits claims to sovereignty or appropriation of celestial bodies, the lack of clarity regarding who can own space resources, that is, the remaining legal vacuum, was filled by some countries at their own discretion.   Aim and tasks. To identify gaps in international space legislation. To analyze existing international treaties in the field of space law and national laws of countries.   Methods. The historical-legal, formal-legal and comparative-legal methods of research are applied.   Results. It is argued that international agreements are outdated legal acts of the Cold War era and do not reflect modern political and technological realities. It was revealed that there are no international legal acts regulating the activities of non-governmental private organizations in the development of space resources for commercial purposes. Active development of national laws, as well as an increase in the pace of commercialization of the space sector are noted. Domestic space laws, in order not to contradict the prohibition of the Outer Space Treaty, allow property claims only for resources that can be extracted from celestial bodies. As a result of such an approach, the priority of international law may be under threat. The increasing commercial focus of the laws of the USA, Luxembourg and Japan is critically assessed. The absence of clear national legislation in China, Russia, India regulating space operations related to the extraction of resources from celestial bodies was revealed. The issue of space pollution in orbit, compensation for environmental damage caused by satellites, fair distribution of radio frequency spectrums and the danger of private aerospace companies being involved in military conflicts is raised.   Conclusions. It is concluded that modern space governance initiatives are more focused on bilateral relations than on international consensus. It is proposed to develop and introduce mandatory restrictions and prohibitions on commercial exploitation of space by international treaties.